2021
DOI: 10.23937/2643-4474/1710056
|View full text |Cite
|
Sign up to set email alerts
|

Cervical Spondylotic Myelopathy: An Updated Review

Abstract: Cervical spondylotic myelopathy (CSM) is a common cause of spinal cord dysfunction. The degenerative disease can cause serious neurological symptoms that can significantly affect the quality of life. The heterogenous presentation of CSM and a lack of a single comprehensive outcome instrument can make the management of suspected CSM very difficult. Despite the advances in surgical techniques to treat CSM, the indications to do surgery remain controversial, particularly in older individuals who commonly present … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 41 publications
(53 reference statements)
0
1
0
Order By: Relevance
“…On the other hand, they reported that there was a knowledge gap in the selection of therapeutic options for mild DCM. Meanwhile, studies on the optimal surgical approach method in patients with DCM who decided to undergo surgery have also been reported ( 9 ). Several studies have compared outcomes after anterior and posterior surgical approaches (ASA and PSA, respectively) for DCM; however, no clear evidence of superiority has been established to date ( 5 ).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, they reported that there was a knowledge gap in the selection of therapeutic options for mild DCM. Meanwhile, studies on the optimal surgical approach method in patients with DCM who decided to undergo surgery have also been reported ( 9 ). Several studies have compared outcomes after anterior and posterior surgical approaches (ASA and PSA, respectively) for DCM; however, no clear evidence of superiority has been established to date ( 5 ).…”
Section: Introductionmentioning
confidence: 99%